2013
DOI: 10.1371/journal.pone.0071532
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Antibiotics for Endoscopy-Associated Peritonitis in Peritoneal Dialysis Patients

Abstract: IntroductionContinuous ambulatory peritoneal dialysis (CAPD) peritonitis may develop after endoscopic procedures, and the benefit of prophylactic antibiotics is unclear. In the present study, we investigated whether prophylactic antibiotics reduce the incidence of peritonitis in these patients.Patients and methodsWe retrospectively reviewed all endoscopic procedures, including esophagogastroduodenoscopy (EGD), colonoscopy, sigmoidoscopy, cystoscopy, hysteroscopy, and hysteroscopy-assisted intrauterine device (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
2
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 24 publications
3
62
2
12
Order By: Relevance
“…The use of periprocedural antibiotics is predicated on the observation that a number of procedures have been associated with an increased risk of peritonitis [26,27]. For example, there have been several reports of peritonitis due to enteric organisms following a lower gastrointestinal Number of facilities 18 20 28 22 17 65 Antibiotics at home prior to seeking medical attention, % Yes, all patients 6 10 0 0 0 40 Yes, some patients 0 20 15 5 6 11 No patients 94 70 85 96 94 49 After-hours nurse provides care at PD facility, % 7 25 33 55 12 endoscopy procedure [26,28]. The significant variation that we observed in the use of periprocedural antibiotics may relate to the limited evidence that exists to support these recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…The use of periprocedural antibiotics is predicated on the observation that a number of procedures have been associated with an increased risk of peritonitis [26,27]. For example, there have been several reports of peritonitis due to enteric organisms following a lower gastrointestinal Number of facilities 18 20 28 22 17 65 Antibiotics at home prior to seeking medical attention, % Yes, all patients 6 10 0 0 0 40 Yes, some patients 0 20 15 5 6 11 No patients 94 70 85 96 94 49 After-hours nurse provides care at PD facility, % 7 25 33 55 12 endoscopy procedure [26,28]. The significant variation that we observed in the use of periprocedural antibiotics may relate to the limited evidence that exists to support these recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Since some invasive procedures are associated with a higher risk of peritonitis, it is recommended that invasive procedures should be accompanied by antibiotic prophylaxis (Renal Association: Evi dence 1C; ISPD: Evidence 2C prior to colonoscopy and 2D prior to invasive gynaecologic procedures) 56,68 . One retrospective observa tional study showed a lower peritonitis rate associated with antibiotic prophylaxis before most endoscopic interventions (colonoscopy, sigmoidoscopy, cystoscopy, hysteroscopy, and hysteroscopy assisted intrauterine device implantation or removal) 88 . However, the best choice for antibiotic prophylaxis is unknown, as there are no studies analysing this question.…”
Section: Antibiotic Prophylaxismentioning
confidence: 99%
“…Allerdings sollten biokompatible Lösungen heutzutage aus anderen Gründen (Erhalt der Restnierenfunktion, Inzidenz der enkapsulierenden peritonealen Sklerose (EPS)) bevorzugt eingesetzt werden [15,16]. Vor einer Koloskopie beziehungsweise bei invasiven gynäkologischen Eingriffen sollte ebenfalls eine Antibiotikaprophylaxe durchgeführt werden [17].…”
Section: Prävention Der Pd-assoziierten Peritonitisunclassified